Quantitative proteomic analysis of G-protein signallingin Stagonospora nodorum using isobaric tags forrelative and absolute quantification - Casey, T.; Solomon, P.; Bringans, S.; Tan, Kar-Chun; Oliver, Richard; Lipscombe, R. (Wiley - VCH Verlag GmbH & Co. KGaA, 2010)
The G protein a-subunit (Gna1) in the wheat pathogen Stagonospora nodorum has previouslybeen shown to be a critical controlling element in disease ontogeny. In this study, iTRAQ and2-D LC MALDI-MS/MS have been used to characterise protein expression changes in the S.nodorum gna1 strain versus the SN15 wild-type. A total of 1336 proteins were identified. Theabundance of 49 proteins was significantly altered in the gna1 strain compared with the wildtype.Gna1 was identified as having a significant regulatory role on primary metabolicpathways, particularly those concerned with NADPH synthesis or consumption. Mannitoldehydrogenase was up-regulated in the gna1 strain while mannitol 1-phosphate dehydrogenasewas down-regulated providing direct evidence of Gna1 regulation over this enigmaticpathway. Enzymatic analysis and growth assays confirmed this regulatory role. Severalnovel hypothetical proteins previously associated with stress and pathogen responses wereidentified as positively regulated by Gna1. A short-chain dehydrogenase (Sch3) was alsosignificantly less abundant in the gna1 strains. Sch3 was further characterised by genedisruption in S. nodorum by homologous recombination. Functional characterisation of thesch3 strains revealed their inability to sporulate in planta providing a further link to Gna1signalling and asexual reproduction. These data add significantly to the identification of theregulatory targets of Gna1 signalling in S. nodorum and have demonstrated the utility ofiTRAQ in dissecting signal transduction pathways.